CMV Ileitis: To Treat or Not to Treat? Implications of Initiating Biologic Therapy for Concurrent Crohn’s Disease - Kendra T. Stilwell; Jason Estes; Maria T. Kurtz; James M. Francis; David T. Lynch; Anish A. Patel (Case Reports in Gastrointestinal Medicine)
Cytomegalovirus (CMV) enteritis is traditionally thought to be a self-limited infection in immunocompetent individuals. Consequently, current guidelines recommend against treating nonimmunocompromised patients with antiviral therapy. Conversely, recent data suggests that spontaneous resolution occurs less frequently than previously believed; furthermore, mortality rate in immunocompetent individuals is similar to that of the immunosuppressed. We present a case of a 43-year-old male who was simultaneously diagnosed with CMV ileitis and Crohn’s Disease. When discovered concomitantly, there is no guidance in the current medical literature regarding the benefit of antiviral treatment of the CMV infection prior to initiating biologic therapy versus the risks of withholding treatment, as is currently recommended for nonimmunosuppressed individuals.